SMU launches two innovative sustainability programmes – Postgraduate Master of sustainability and undergraduate second major in sustainable societies - Singapore Management University (Institutional Knowledge at Singapore Management University, 2023)
Singapore Management University (SMU) will launch a new Master of Sustainability (MST) (永续发展硕士课程) and a Second Major in Sustainable Societies (SSOC) (可持续社会第二主修) as part of a suite of sustainability courses and programmes to develop sustainability leaders and meet the needs of a green economy. The MST is jointly helmed by the School of Social Sciences (SOSS) and College of Integrative Studies (CIS), and SSOC is being offered by the School of Social Sciences as a second major available to all SMU undergraduates.